Non-invasive optical coherence tomography with in depth analysis of modalities : fourier domain and polarization sentivity - Nivetha Narayanasamy (2014)
Optical Tomography was invented at the beginning years of 1980s and branched into various approaches. One such approach is the optical coherence tomography (OCT). This report will delve deeper onto the faction of OCT investigating the principles of OCT as well as the practical application of OCT that can be a useful imaging technique in the future. So far, research in this area has shown tremendous therapeutic potential that can be transformed into reality in the near future. Optical techniques are evolving to be increasingly popular in the medical industry due to its non-invasive and therefore safer and cheaper nature compared to other imaging techniques.